Mark's Jesus, divine?: a study of aspects of Mark's christology with special reference to Hebrew divine warrior traditions in Mark, and in relation to contemporary debates on primitive christology - Throup, Marcus (2014)
Within the wider framework of contemporary debates on primitive NT Christology concerning the early Christians’ perception of the divinity of Jesus, this work investigates the influence of Hebrew Divine Warrior Traditions (HDWT) on the Markan sea-miracles (Mark 4.35-41; 6.45-52) and exorcisms (Mark 1.21-28; 5.1-20; 7.24-30; 9.14-29). In a final form, narrative approach to the Markan text, this study seeks to demonstrate that as part of his “high” Christology, Mark draws on the HDWT in such a way as to liken Jesus to God the Divine Warrior in “Old Testament” and Second Temple Jewish texts. The present work argues that in the sea-miracles and exorcisms, Mark transfers divine attributes and operations to Jesus, claiming some form of divine identity for Jesus. The findings of this study are then considered in terms of their implications for Mark’s Christology, and located in relation to the work of leading scholars on primitive Christology in general.